OTOP and OVOP: An Analysis of Placing a Value on Development - Jaiborisudhi, Watunyu (Thai Journal of East Asian Studies, 2019)
This research article is a part of the research project "A Study on One Tambon One Product (OTOP) Project under the Product Discourse: Possibilities and Challenges of Building Human Security within Community". It employs a mix method conducting both quantitative and qualitative research with main purposes of examining a power process that directs and controls OTOP towards the product discourse and also analyzing possibilities and challenges of building human security within community. The quantitative study shows most population well perceive OTOP as a good or product made within local community at a good to an excellent levels, totally accounted for 87.8 % (at a good level for 53.3% and at an excellent level for 34.5%). They also perceive that OTOP is promoted by the government as a local product more than as a human resource development scheme at a good to an excellent levels, totally accounted for 79.2% (at a good level for 40.2 % and at an excellent level for 39.0%). In qualitative study, the researcher further compares OTOP project with One Village One Product (OVOP) process of Oita prefecture in Japan to find out how is the difference in placing a development value between OTOP project and OVOP process by conducting a discourse analysis. The research shows both schemes are resulted from an economic problem caused by the capitalist development, but place different values on development. OTOP mainly place a development value on a tangible product, while OVOP put on human resource development. It further reveals a power process that directs and controls OTOP towards the product discourse and OVOP towards human resource development discourse. The power process has reproduced these discourses which eventually become a public perception. It reflects that this power process determines to place a development value on a specific goal more than others. In case of OTOP, the product discourse which created and promoted by mechanisms and power structures, reduces values and construct otherness on human resource development. It eventually leads to a problem of building human security within community.